Strong correlation between standing cough test and 24‐hour pad weights in the evaluation of male stress urinary incontinence. Issue 1 (6th November 2019) - Yi, Yooni A.; Keith, Christopher G.; Graziano, Christopher E.; Davenport, Michael T.; Bergeson, Rachel L.; Christine, Brian S.; Morey, Allen F.
Abstract: Aims: We sought to compare in‐office physical exam findings via standing cough test (SCT) versus 24‐hour pad weights among men seeking treatment for postprostatectomy stress urinary incontinence (SUI). Methods: A retrospective review of a single surgeon database of incontinence procedures was performed. Documentation of SUI severity (grades 0‐4) was completed by SCT preoperatively utilizing the Male Stress Incontinence Grading Scale (MSIGS). All patients had pads per day (PPD) and 24‐hour pad weights obtained. We determined the Spearman's correlation coefficient between these variables. Results: We identified 104 men who underwent anti‐incontinence surgery (AdVance Sling or artificial urinary sphincter [AUS]). In the sling group (65 patients), nearly all (97%) had minimal incontinence with SCT (MSIGS = 0‐2). In the AUS group (39 patients), most patients (69%) had an MSIGS 3 or 4 with SCT. Spearman's coefficient between quantification of SCT and pad weight for the overall group was ρ = .68 ( P < .0001) demonstrating a strong positive correlation. PPD was also strongly correlated with pad weight ( ρ = .55, P < .0001). As seen previously, SCT and PPD were correlated ( ρ = .47, P < .0001). In a multivariable model predicting pad weight, the effect of SCT was greater than PPD ( β = 83 [54‐111], P < .0001 vs 45 [2169], P = .0004). Conclusions: SCT findings strongly correlate to 24‐hour pad weights in the evaluation of male SUI. The SCT shows promise as a rapid, reliable, noninvasive measure of SUI severity before anti‐incontinence surgery.